Data collection and analysis methods for effective municipal energy management - Kopets, Halyna (Видавництво Львівської політехніки, 2010)
This article discusses the issues of the methods of collection and data analysis for municipal energy management.
Keywords: information collection and analysis; computer systems; the municipal energy management